Сучасні досягнення фізіотерапевтичного лікування больового синдрому у хворих із патологічними процесами в щелепно-лицевій ділянці - Мокрик, О.Я.; Назаревич, М.Р. (Медична гідрологія та реабілітація, 2012)
Представлен литературный обзор современных методов физиотерапевтического лечения долевого синдрома у больных с патологическими процессами воспалительного и травматического генеза в челюстно-лицевой области, а также с прозопалгиями. Описаны методики физиотерапевтического лечения болевого синдрома, использованные авторами обзора. The article deals with a literary review of modern methods of physiotherapy treatment of pain syndrome in patients with pathological processes of inflammatory and traumatic genesis in maxillofacial area and prosopalgia. The analysis of the results obtained by the authors was given. The own methods of physical therapy of pain syndrome were described.